Limit properties of the solutions of a Dirichlet problem in an elliptic domain - Voroshik, N. I.; Gorbaichuk, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study solutions of a Dirichlet problem in a fixed ellipse and their behavior in the integral metric in the case where interior points approach the boundary of the ellipse.